A COMPARATIVE STUDY BETWEEN ONE BATH DYEING METHOD FOR POLYESTER COTTON (PC) BLENDED FABRIC OVER CONVENTIONAL TWO BATH DYEING METHOD - Ripon Kumar Prasad; Md. Abdus Shahid; , Nurunnabi; Marzia Dulal (European Scientific Journal, ESJ, 2015)
Dyeing of Polyester Cotton (PC) blended knit fabrics is done by two different types of dyestuff namely reactive dyes for cotton part and disperse dyes for polyester part in conventional two bath method where after polyester part dyeing the liquor is drained and then cotton part is dyeing. This research work has been carried out on finding the possibility of dyeing this type of fabric in single bath method without drain the liquor after enzyme bio-polishing and polyester part dyeing. No extra chemicals are needed in one bath dyeing method. There is in significant change of fastness properties than conventional two bath method. This one bath dyeing method saves the consumption of water with energy and time. In this research work, it was found that in one dyeing method cost and time are saved to conventional two bath dyeing method.